(untitled) (Cambridge, 1999)
What are the best ways to do research on the psychology of women and gender? This volume illustrates a variety of innovative approaches to knowledge, applying them to diverse issues: violence against girls and women, sexuality, life patterns, educating against sexism and more. Moreover, it explores the role of personal values and social forces on the research process. Over sixty international contributors and a comprehensive resource guide make this an essential resource for researchers and educators.
Keywords: Psychology,Psychology, Experimenta,Feminist psychology,Tâm lý,Thí nghiệm tâm lý,Tâm lý học nữ quyền; Research,Methodology,Nghiên cứu,Phương pháp